Disease, Religion and Healing in Asia: Collaborations and Collisions - Vargas-O'Bryan, Ivette M. (Taylor and Francis, 2014)
Recent academic and medical initiatives have highlighted the benefits of studying culturally embedded healing traditions that incorporate religious and philosophical viewpoints to better understand local and global healing phenomena. Capitalising on this trend, the present volume looks at the diverse models of healing that interplay with culture and religion in Asia.Cutting across several Asian regions from Hong Kong to mainland China, Tibet, India, and Japan, the book addresses healing from a broader perspective and reflects a fresh new outlook on the complexities of Asian societies and their